2015
DOI: 10.1016/j.jsat.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Interventions for Homeless Youth Evidencing Substance Use Disorders: Results of a Randomized Clinical Trial

Abstract: While research on homeless adolescents and young adults evidencing substance use disorder is increasing, there is a dearth of information regarding effective interventions, and more research is needed to guide those who serve this population. The current study builds upon prior research showing promising findings of the Community Reinforcement Approach (CRA) (Slesnick, Prestopnik, Meyers, & Glassman, 2007). Homeless adolescents and young adults between the ages of 14 to 20 years were randomized to one of three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 77 publications
(100 reference statements)
3
52
0
1
Order By: Relevance
“…Although including youth aged 16 to 17 years would have more accurately reflected existing services for homeless youth, differences in legal status for tenancy and, in some jurisdictions, informed consent make "Housing First" more complicated to study and implement in youth <18 years. These findings may not be generalizable to young people 7 CIS, Community Integration Scale psychological integration subscale with possible scores ranging from 4 to 20 (higher scores indicate higher level of integration); CSI, Colorado Symptom Index, a measure of psychiatric symptomatology with possible scores ranging from 5 to 70 (higher scores indicate more severe mental health symptoms); ED, emergency department; EQ-5D, EuroQoL5 Dimensions Visual Analog Scale, a measure of generic quality of life scored from 0 (worst imaginable health state) to 100 (best imaginable health state); GAIN-SPS, Global Assessment of Individual Needs Short Screener-Substance Problem Scale, a measure of substance use problems over the previous month, with possible scores ranging from 0 to 5 (higher scores indicate more symptoms of substance misuse); MCAS, Multnomah Community Ability Scale, a measure of community functioning with possible scores range from 17 to 85 (higher scores indicate a higher level of community functioning); QOLI-20, a measure of condition-specifi c quality of life with total possible scores ranging from 20 to 140 and subscale scores ranging as follows: family (4-28), fi nances (2-14), leisure (5-35), living situation (1-7), safety (4-28), social (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), and overall quality of life (1-7), with higher scores indicating higher quality of life; RAS, Recovery Assessment Scale, a measure refl ecting various components of recovery with possible scores ranging from 22 to 110 (higher scores indicate higher degree of recovery); SF-12, Short Form 12 survey, a measure of physical and mental health status assessed by the physical component summary and mental health component summary, both of which range from 0 to 100 (higher scores indicate better health status). a Models included treatment group (reference: treatment as usual), time (month of visit; reference: baseline), study city (reference: Winnipeg), Aboriginal and ethnoracial status (reference: non-Aboriginal/non-ethnoracial), and treatment × time interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although including youth aged 16 to 17 years would have more accurately reflected existing services for homeless youth, differences in legal status for tenancy and, in some jurisdictions, informed consent make "Housing First" more complicated to study and implement in youth <18 years. These findings may not be generalizable to young people 7 CIS, Community Integration Scale psychological integration subscale with possible scores ranging from 4 to 20 (higher scores indicate higher level of integration); CSI, Colorado Symptom Index, a measure of psychiatric symptomatology with possible scores ranging from 5 to 70 (higher scores indicate more severe mental health symptoms); ED, emergency department; EQ-5D, EuroQoL5 Dimensions Visual Analog Scale, a measure of generic quality of life scored from 0 (worst imaginable health state) to 100 (best imaginable health state); GAIN-SPS, Global Assessment of Individual Needs Short Screener-Substance Problem Scale, a measure of substance use problems over the previous month, with possible scores ranging from 0 to 5 (higher scores indicate more symptoms of substance misuse); MCAS, Multnomah Community Ability Scale, a measure of community functioning with possible scores range from 17 to 85 (higher scores indicate a higher level of community functioning); QOLI-20, a measure of condition-specifi c quality of life with total possible scores ranging from 20 to 140 and subscale scores ranging as follows: family (4-28), fi nances (2-14), leisure (5-35), living situation (1-7), safety (4-28), social (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), and overall quality of life (1-7), with higher scores indicating higher quality of life; RAS, Recovery Assessment Scale, a measure refl ecting various components of recovery with possible scores ranging from 22 to 110 (higher scores indicate higher degree of recovery); SF-12, Short Form 12 survey, a measure of physical and mental health status assessed by the physical component summary and mental health component summary, both of which range from 0 to 100 (higher scores indicate better health status). a Models included treatment group (reference: treatment as usual), time (month of visit; reference: baseline), study city (reference: Winnipeg), Aboriginal and ethnoracial status (reference: non-Aboriginal/non-ethnoracial), and treatment × time interaction.…”
Section: Discussionmentioning
confidence: 99%
“…2 Despite this, few interventions for homeless youth have been empirically tested, 2,4 and even fewer have targeted housing outcomes. Case management, a strategy used widely with homeless youth, has demonstrated improvements in housing stability over time, but did not separate from other active treatments 5 or treatment as usual. 6 The Community Reinforcement Approach, an operant-based behavior therapy tested in 2 randomized controlled trials in homeless youth, was associated with a reduction of days homeless 5 and increased social stability (a measure which included housing), 7 but with only the latter trial demonstrating improvement relative to a comparison group, it is not clear that any empirically tested interventions have impacted youth's housing stability beyond general support and the passage of time.…”
mentioning
confidence: 99%
“…39, 40 Health care services for homeless adolescents include: 1) community reinforcement approach, an operant-based behavioral intervention that helps youth develop alternative reinforcing behaviors and plans to avoid negative environmental situations; 2) motivational enhancement therapy, a form of motivational interviewing that includes interviewer feedback; and 3) case management that typically involves case managers linking youth to resources within their community. 41 All three interventions have demonstrated similar efficacy in reducing substance use and associated problems. 41 Policy-level interventions for alcohol have also been shown to reduce violence and other harms associated with alcohol use among youth.…”
Section: Discussionmentioning
confidence: 98%
“…41 All three interventions have demonstrated similar efficacy in reducing substance use and associated problems. 41 Policy-level interventions for alcohol have also been shown to reduce violence and other harms associated with alcohol use among youth. 42 One recent study found that ambulance pickups for violent injuries among high-risk youth aged 15–24 were significantly reduced after introduction of alcohol license restrictions in Richmond, Virginia.…”
Section: Discussionmentioning
confidence: 98%
“…The treatment sessions focus on guiding families to consider their current problems and solutions through techniques such as reframing and interpretations, interrupting problem behaviors through communication and problem-solving skills training, and assisting families in obtaining services such as medical care, job trainings, or self-help programs. Originally developed for substance using runaway adolescents and their families, (Slesnick, Guo, Brakenhoff, & Bantchevska, 2015; Slesnick & Prestopnik, 2005, 2009), the intervention has been rated as a promising evidence-based practice by the National Institute of Justice and as a supported evidence-based practice by the California Evidence-Based Clearinghouse. Even though EBFT has been effective for families with a substance using adolescent runaway, the effectiveness of EBFT for mothers seeking substance use treatment and their children has not been tested.…”
Section: Methodsmentioning
confidence: 99%